Effect of modal analysis on vibration reduction of hollow aluminum alloy profiles. Issue 3 (April 2021) - Qin, Dezhao; Wu, Binghui; Song, Chang; Shan, Jian; Chen, Naichao; Wu, Maoliang
Abstract: Through the classification of the noise types in the train, this paper discusses the influence of the car body profile structure on the vibration reduction and noise reduction in the train compartment, introduces the principle and advantages of modal analysis in the natural frequency analysis of the object, attempts to use the modal analysis function of ANSYS software to analyze the natural frequency and mode of the complex hollow aluminum alloy profile structure, and finds out the relevant parameter changes. The influence of chemical on the overall vibration reduction and noise reduction effect of profiles.